The response of microalgal biomass and community composition to the chemical and physical dynamics of two Eastern Cape estuaries - Cotiyane, Phumlile L (Rhodes University, Faculty of Science, Botany Department, 2017)
Water quality characteristics of estuaries are influenced by both natural and anthropogenic activities. Estuaries situated in coastal urban areas are exposed to more perturbations than those in rural settings. This study determined the drivers of phytoplankton biomass and community composition in two Eastern Cape estuaries and evaluated the anthropogenic activities that influence the overall health of each estuary. The estuaries were sampled in summer and winter (2014, 2015). The water quality of the estuaries was determined by measuring the variability in physico-chemical parameters (salinity, temperature, dissolved oxygen and pH), nutrients, phytoplankton biomass and composition and faecal bacteria. Results show that both Mngazana and Nahoon are well oxygenated (~ 6.0 mg l-¹) and are saline systems (~ 35 ppt) due to low freshwater inputs into both estuaries. Mngazana Estuary exhibited low nutrient inputs along the length of the estuary including Creeks 1 and 2 with low chlorophyll a (4.0 ± 0.2 µg Chl-a r¹) being recorded during this study while Nahoon Estuary had an overall chlorophyll a of 3.5 ± 0.3 µg Chl-a r¹. The two estuaries were dominated by flagellates with phytoplankton blooms recorded seasonally. Possible eutrophic conditions were evident along the upper reaches of Nahoon indicated by nutrient accumulation and by the presence of cyanobacteria. This also this reflected the possible anthropogenic nutrient inputs originating from the Nahoon catchment despite the low freshwater inflow. The presence of faecal bacteria counts along both estuaries indicates the need for further investigation into the source of faecal contamination. The use of nutrient analyses and phytoplankton composition during this study enabled a clear description of the water characteristics of the investigated estuaries. Furthermore, the need for the adherence to freshwater flow requirements of estuaries to limit the dominance of marine waters was clearly illustrated. Urban runoff due to impervious surfaces increases nutrient inputs into estuaries while rural use of estuarine waters introduces contaminants into the system; coupled with low freshwater inputs and eutrophic conditions, the deterioration of estuarine water quality over time demonstrates the need for effective monitoring of these systems.
Keywords: Estuarine plants -- South Africa -- Eastern Cape; Estuarine ecology -- South Africa -- Eastern Cape; Phytoplankton -- South Africa -- Eastern Cape; Algal blooms -- South Africa -- Eastern Cape; Algal blooms -- Monitoring-- -- South Africa -- Eastern Cape